2022
DOI: 10.1021/acs.jpcc.2c00166
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism Induced by the Coupling between Surface Plasmon Polaritons and Localized Surface Plasmon Resonances in a Double-Layer Complementary Nanostructure

Abstract: Circular dichroism (CD) spectroscopy is an important technique for detecting and identifying chiral molecules in the fields of chemistry, biology, and other life sciences. Artificial plasmonic nanostructures exhibit considerable CD effects, but the preparation of 3D and multilayer chiral structures that exhibit large CD signals is usually difficult. Strong CD effects and simple fabrication processes are necessary. In this study, double-layer complementary nanostructures (DLCNs) that can generate prominent CD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The prospects of these applications have triggered the study and characterization of a variety of periodic arrays supporting chiral lattice resonances. The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, , such as helices, or multiple nanostructures forming a chiral arrangement. , As expected, the lattice resonances supported by these systems exhibit different responses under illumination with right- and left-handed circularly polarized light. More recently, it has been shown that the combination of a rectangular lattice with an achiral unit cell results in arrays capable of supporting lattice resonances with some degree of chirality, which can be enhanced by positioning the array in an inhomogeneous dielectric environment .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The prospects of these applications have triggered the study and characterization of a variety of periodic arrays supporting chiral lattice resonances. The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, , such as helices, or multiple nanostructures forming a chiral arrangement. , As expected, the lattice resonances supported by these systems exhibit different responses under illumination with right- and left-handed circularly polarized light. More recently, it has been shown that the combination of a rectangular lattice with an achiral unit cell results in arrays capable of supporting lattice resonances with some degree of chirality, which can be enhanced by positioning the array in an inhomogeneous dielectric environment .…”
Section: Introductionmentioning
confidence: 92%
“…56−64 The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, [56][57][58]63 such as helices, 60 or multiple nanostructures forming a chiral arrangement. 65,66 circularly polarized light. More recently, it has been shown that the combination of a rectangular lattice with an achiral unit cell results in arrays capable of supporting lattice resonances with some degree of chirality, which can be enhanced by positioning the array in an inhomogeneous dielectric environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Areas other than the chiral L hole were then scanned using electron beam exposure. 20 The subsequent development, fixation, and drying subsequently yield chiral nanorods of the same size as the chiral L-shaped hole. Later, SiO 2 and Si layers were deposited alternately on the substrate and applied to the samples.…”
Section: Chiral Structure and Computational Methodsmentioning
confidence: 99%
“…The following steps can be taken to achieve the structure mentioned above: First, the complementary chiral nanopore array to the chiral nanorod array is prepared on the gold substrate by electron beam lithography technology. 35 Then, SiO 2 and lithium niobate thin films are alternately deposited on their surface by physical vapor deposition technology. 36 Finally, the excess photoresist around the structure is removed by the peeling method to form MCNAs.…”
Section: Structure Theory and Designmentioning
confidence: 99%